Cultural Influence on Language: Exploring the Intersection of Vocabulary, Grammar, and Communication Styles (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the profound influence of cultural factors on language, examining how vocabulary, grammar, and communication styles reflect the beliefs, customs, and worldview of different societies. Examples from various cultures, including Indigenous communities and African American Vernacular English (AAVE), illustrate the diverse ways in which language serves as a mirror of cultural identity. Through the lens of linguistic relativity, metaphors, and proverbs, as well as taboos and politeness, we delve into the intricate relationship between language and cultural values. Understanding these cultural influences is crucial for effective communication and fostering intercultural understanding in a globalized world.